2020
DOI: 10.3390/su12124845
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Seismic, and Architectural Renovation of RC Framed Buildings with Prefabricated Timber Panels

Abstract: In seismic European countries most of the residential building stock is highly energy-intensive and earthquake-prone because it was built before the enforcement of the most recent energy and seismic codes. Furthermore, this stock often shows a low architectural quality due to poor maintenance and/or construction and design deficiencies: for all these reasons, it needs deep renovation, but the use of common energy and seismic upgrading techniques is often unsustainable in terms of costs, work duration, and occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 23 publications
(28 reference statements)
0
50
0
Order By: Relevance
“…Previous research [55] by the authors indicated that Bosnia-Herzegovina and Slovenia have almost identical energy savings when comparing refurbishment of the entire building envelope for the same type of building (e.g., MFH-multifamily houses-and AB-apartment buildings), which would be adequate for renovation with renewable materials when analyzing the possibility of using prefabricated panels such as Timber Energy System (TES) [56], Building Energy Renovation Through Timber Prefabricated Module (BERTIM) [57], or energy, seismic, and architectural renovation through Prefabricated Timber Panels (PTP) [58].…”
Section: Discussion Of Bosnia-herzegovina and Slovenia Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research [55] by the authors indicated that Bosnia-Herzegovina and Slovenia have almost identical energy savings when comparing refurbishment of the entire building envelope for the same type of building (e.g., MFH-multifamily houses-and AB-apartment buildings), which would be adequate for renovation with renewable materials when analyzing the possibility of using prefabricated panels such as Timber Energy System (TES) [56], Building Energy Renovation Through Timber Prefabricated Module (BERTIM) [57], or energy, seismic, and architectural renovation through Prefabricated Timber Panels (PTP) [58].…”
Section: Discussion Of Bosnia-herzegovina and Slovenia Casesmentioning
confidence: 99%
“…The previous sections demonstrated that the use of renewable materials in energy refurbishments in B&H and Slovenia is rather uncommon and remains off the radar of policymakers. Even if it is a relevant topic in different countries, with some successful technological solutions being developed (for example, TES, BERTIM, MORE-CONNECT, and CLT panel façade systems) [56][57][58]65], there has not been a general breakthrough leading to a wider use of such solutions in the analyzed countries. However, mentioned prefabricated solutions have significant potential, yet there are still gaps in understanding their possible use for energy refurbishment.…”
Section: Analysis Of the Barriers Preventing Wider Use Of Renewable Mmentioning
confidence: 99%
“…(Buonocore et al, 2014). Today, wood and the modern materials derived from it can represent an optimal choice for interventions of volumetric additions (Margani et al, 2020;Valluzzi et al, 2021). Modern research and technological innovations have allowed overcoming the problems related to the anisotropy of the original material by creating a "new generation" of products and technologies that fully compete with the most commonly used materials (Di Gennaro et al, 2019;Frunzio et al, 2021;Izzi et al, 2018;Sun et al, 2020).…”
Section: Parasite Architecture: Structural Aspectsmentioning
confidence: 99%
“…Another innovative energy, seismic and architectural retrofit strategy for RC framed buildings is based on the external addition of cross-laminated timber panels to the outer walls, in combination with wooden-framed panels. As recently proposed by Margani et al [25], these prefabricated panels are connected to the existing structure through special seismic energy dissipation devices, and they also integrate insulation and cladding materials to improve both energy performance and architectural image.…”
Section: The State Of Art Of Combined Retrofit Interventionsmentioning
confidence: 99%